Broiler Chicken Marketing Channels in Kabawo District Muna Regency - Idul Lafi; Surni Surni; Agustono Slamet (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2023)
This research is motivated by the sale and purchase of broiler chickens by farmers with traders in the Kabawo District of Muna Regency. This study aims to (1) find out the marketing channels of broiler chickens in Kabawo District of Muna Regency and (2) know the level of efficiency of broiler chicken marketing in Kabawo District of Muna Regency. This research was analyzed using descriptive analysis, margin analysis, and marketing efficiency (Farmer's Share). Determination of breeder and trader samples is carried out by census sampling, namely collecting the entire population as a research sample if the population is less than 50 people. The population in this study consists of 10 breeders, 1 collecting merchant, and 1 retailer in the Kabawo District of Muna Regency. The results of research that has been carried out are obtained as follows: (1) marketing channels involved in the marketing process from farmers to consumers, namely (a) marketing channel I, where the farmer sells his chickens to the retailer merchant, then the retailer forwards the sale directly to the end consumer and (b) the marketing channel II where the farmer sells his chicken to the collecting merchant, and then the collecting merchant forwards the sale to the end consumer. (2) marketing margin and percentage share of prices received by farmers (farmer's share) broiler chickens in Kabawo District muna regency run efficiently, where each channel shows with a farmer value s share above 50%, namely marketing channel I of 86.49% and marketing channel II of 80%.